2014
DOI: 10.1002/jbm.a.35127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental mechanics of magnetic microparticle-induced strain on fibrin clots

Abstract: In this study, a novel technique was developed in which magnetic microparticles (MMPs) and quantum dots (QDs) were successfully incorporated into fibrin clots. The MMPs were added at concentrations of 0.1 wt% and 1 wt% of the fibrin content in an effort to determine if a magnetic field could be utilized to mechanically stretch the fibrin network, simulating how cells may invade a network. The QDs were added at a dilute concentration of 0.1 wt% to determine if the mechanical properties of the fibrin network wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In the preclinical study, it was reported that QDs were useful to label and were applied to flow cytometry analyses of thrombosis in the blood plasma of human subjects [38]. In addition, Averett reported that QDs can label a clot in the fibrin network only in the presence of matrix metalloprotease and thrombin [39]. These reports support our findings that QDs are useful to label clots in blood vessels of thrombotic condition.…”
Section: Resultssupporting
confidence: 88%
“…In the preclinical study, it was reported that QDs were useful to label and were applied to flow cytometry analyses of thrombosis in the blood plasma of human subjects [38]. In addition, Averett reported that QDs can label a clot in the fibrin network only in the presence of matrix metalloprotease and thrombin [39]. These reports support our findings that QDs are useful to label clots in blood vessels of thrombotic condition.…”
Section: Resultssupporting
confidence: 88%
“…Cells embedded into extracellular matrix can induce stiffening of fibrin gels via myosin-driven cell contraction, which may be important for a number of patho(physiological) conditions, such as wound healing and cancer genesis [55]. Fibrin elasticity can be modulated by other physical [56-58] or biochemical [59, 60] modifications as well as by blood components incorporated into the fibrin network [60-62]. …”
Section: Non-linear Elasticity and High Deformability Of Fibrinmentioning
confidence: 99%
“…Figure 1 displays the configuration in relation to the fibrin matrix sample, as well as its relative position in the confocal microscope platform. The SolidWorks drawing of the microscope is based on measurements taken of the actual Zeiss 700 B confocal microscope located at the Georgia Institute of Technology, which is the same confocal microscope used in the previous experimental fibrin/MMP study [9]. The microscope uses a platform that has adjustable sliders to capture the sample slide, which allow the solenoids to maneuver vertically in the open space.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Utilizing the magnetic field and flux density, the electromagnetic forces acting on a material using Maxwell's stress tensor were calculated using (9). For the current study, under vacuum conditions in the absence of moving charges (9) reduces to (10).…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation